2018
DOI: 10.1016/j.trb.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Decision field theory: Improvements to current methodology and comparisons with standard choice modelling techniques

Abstract: There is a growing interest in the travel behaviour modelling community in using alternative methods to capture the behavioural mechanisms that drive our transport choices. The traditional method has been Random Utility Maximisation (RUM) and recent interest has focussed on Random Regret Minimisation (RRM), but there are many other possibilities. Decision Field Theory (DFT), a dynamic model popular in mathematical psychology, has recently been put forward as a rival to RUM but has not yet been investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 63 publications
0
40
0
Order By: Relevance
“…What is more, it can also accurately predict the relationship between the probability of selection and preference with time. Besides, it is widely applied in the fields of military command control and traffic control [43].…”
Section: A the Classical Dft Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, it can also accurately predict the relationship between the probability of selection and preference with time. Besides, it is widely applied in the fields of military command control and traffic control [43].…”
Section: A the Classical Dft Methodsmentioning
confidence: 99%
“…Besides, the DFT method can accurately predict the selection probability and present the relationship between preference intensity and time. It has been applied to stock trading, military command control and traffic control [41]- [43]. However, when the preference information or uncertain knowledge is expressed by the form of HFS, we cannot use the traditional DFT to address it efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The non-linearity in the specification for the drift rates allows for the explanation of the similarity, attraction and compromise effects. Notably, work such as Guevara and Fukushi (2016) and Hancock et al (2018) demonstrate that models that can account for these context effects can be effective for understanding travel behaviour. The corresponding non-linear expression for the drift rate is the second value function we test in this paper:…”
Section: Value Functions: Linear Difference Asymmetric Decay Soft Plusmentioning
confidence: 99%
“…Batley and Dekker (2019) and for regret models, see Dekker 2014). Departures to more different models, such as decision field theory (Busemeyer and Townsend, 1992), whilst sometimes finding improvements in model fit, additionally result in models that become computationally infeasible for large-scale datasets (Hancock et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, research and software for experimental design have almost exclusively been based on the (often implicit) assumption that decision-makers make choices using a (linear-additive) Random Utility Maximisation (RUM) decision rule. However, a growing https://doi.org/10.1016/j.jocm.2019.04.002 Received 8 August 2018; Received in revised form 2 April 2019; Accepted 2 April 2019 number of studies have found overwhelming evidence that decision-makers may opt for other types of decision rules when making choices (Kivetz et al, 2004;Hess et al, 2012;Leong and Hensher, 2012;Guevara and Fukushi, 2016;Hancock et al, 2018;Van Cranenburgh and Alwosheel, 2019). In light of this, very recently a method to create efficient experimental designs for one alternative decision rule, namely Random Regret Minimisation (RRM), has been proposed .…”
Section: Introductionmentioning
confidence: 99%